Grounding AI in practice: What extension gets wrong, what extension gets right, and what AI can learn - Davis, Kristin E.; Jones-Garcia, Eliot; Singaraju, Niyati (International Food Policy Research Institute, 2025)
Generative artificial intelligence (gen AI) applications - which produce text, images, code, and other content based on surfacing patterns in vast datasets - promise many benefits for agrifood systems (e.g., reaching more people at less cost, availability around the clock, real-time data).